From initial teacher training to actual teaching work: understanding the trajectory - Sánchez-Sánchez, Gerardo Ignacio (2018)
This article explores the understanding of pedagogical experiences of 32 teachers from different cohorts during professional practicum. The results show an image of teaching as a human encounter, not only as a technical one, among subjects, contexts, and demands. It is understood as an activity endowed with complexity as a human task and a process that becomes visible within the practicum arena, which develops into a learning as well as a productive crisis source. The qualitative approach was adopted built on the interpretive case study modality; semi-structured interviews and a results discussion strategy based on content analysis were used. The research was conducted on the regional campus of a university, located 200 miles south of Santiago de Chile. The study opens up perspectives for dialogue within the regional context, having the potential to enrich Initial Teacher Training, by means of understanding that there are no ideal models of teachers regardless of the settings or performing frameworks that regulate teaching; this makes it necessary to tune in theoretical training models to the limits and possibilities presented by the teaching practice.